IMPLEMENTASI PELAYANAN PUBLIK DALAM PENYALURAN BANTUAN SOSIAL PADA PROGRAM KELUARGA HARAPAN (PKH) BERDASARKAN UNDANG-UNDANG NO. 13 TAHUN 2011 DI KELURAHAN PANDEGLANG - Nuraeni, Heni; Bangsawan, Try Adhi; Amilia, Rizki (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Based on Law Number 13 of 2011 concerning the Handling of the Poor, the purpose of this study is to describe the implementation of community assistance in the study of Social Assistance through the Family Hope Program (PKH) in Pandeglang Village. This study uses a descriptive qualitative method with a case study approach. Data were collected using semi-structured observation, non- participatory analysis, and document analysis. Information includes PKH facilitators, village officials, and beneficiaries. This study shows that although PKH implementation has followed procedures and laws and regulations, several technical, administrative, and social problems remain. First and foremost, these include a lack of public understanding of the assistance process and human resources, inadequate Integrated Social Welfare Data (DTKS), and suboptimal communication between relevant parties. Inter- agency coordination, preventive activities, and government cooperation are supporting elements. Based on the research findings, although PKH has been implemented in Pandeglang Village, its effectiveness has not been fully realized. Improvements made include increasing public awareness of the rights and obligations of recipients of assistance, clear and concise presentation of the DTKS (Disability Report), and improving the social capacity of facilitators. This study offers theoretical contributions related to public policy implementation and practical recommendations to maximize the quality of social services.